INDIGENIZING PHILOSOPHY: ACCULTURATION AND THE RETAINMENT OF INUIT IDENTITY IN CANADA (Canadian Journal of Native Studies, 2026)
Recently, there has been a political movement by Indigenouspeoples and their allies to decolonize and Indigenize the academy.But often times, so-called allies can do more harm in theirattempts to achieve justice and equality for others because theylack the appropriate knowledge and understandings of thosewhom they aim to aid. One key question that people who areinterested in justice for Indigenous peoples should ask is whatit means to “Indigenize” something. My goal here is to explorewhat it means to ‘Indigenize’ Philosophy by questioning whocan do so, to what extent, and what is required.